2019
DOI: 10.3892/etm.2019.8074
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated miRNA‑182‑5p expression in tumor tissue and peripheral blood samples from patients with non‑small cell lung cancer is associated with downregulated Caspase 2 expression

Abstract: Lung cancer has the highest morbidity and mortality rates among all malignant tumors worldwide. Previous studies demonstrated that microRNA (miR)-182-5p may serve different roles in different types of cancer, including renal cell carcinoma and liver cancer. However, the functional role of miR-182-5p in non-small cell lung cancer (NSCLC) remains unknown. In the current study, the expression level of miR-182-5p in tumor tissue and peripheral blood samples obtained from patients with NSCLC was examined. The biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…An increasing number of studies have reported the important role of miRNAs in the treatment of various human cancers (23)(24)(25). The present study aimed to investigate the expressional patterns of miR-767 in NSCLC clinical samples and cells and to analyze the functional role of miR-767 in tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have reported the important role of miRNAs in the treatment of various human cancers (23)(24)(25). The present study aimed to investigate the expressional patterns of miR-767 in NSCLC clinical samples and cells and to analyze the functional role of miR-767 in tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…The expression level of miRNA-33a plays a vital role in the progression of LUAD; it could be an ideal biomarker for the diagnosis and prognosis of LUAD patients who have received adjuvant chemotherapy [ 10 ]. Upregulated oncogenic miRNAs (miR-130b, miR-182-5p, miRNA-17, and miRNA-222) were reported to cause the development and progression of LUAD [ 11 , 12 , 13 ]; moreover, downregulated miRNAs (miR-486-5p, miR-101, miR-133a), also called tumor-suppressive miRNAs, were reported to repress the development of NSCLC [ 14 , 15 , 16 ]. miR-21 and miR-24 were significantly lower in ASO serum samples of lung carcinoma patients when compared to the samples of BSO patients.…”
Section: Introductionmentioning
confidence: 99%
“…Early peripheral lung cancer has no significant symptoms, and when the symptoms are obvious, the cancer is in a late stage. Globally, lung cancer has a high incidence and mortality rate[ 5 , 6 ]. If patients with peripheral lung cancer have advanced metastasis, it is necessary to have a clear molecular diagnosis based on different targets to initiate individualized treatment and promote a therapeutic effect.…”
Section: Introductionmentioning
confidence: 99%